2017
DOI: 10.1186/s12872-017-0600-8
|View full text |Cite
|
Sign up to set email alerts
|

Aging and obesity are associated with undiagnosed hypertension in a cohort of males in the Central Province of Sri Lanka: a cross-sectional descriptive study

Abstract: BackgroundLifestyle factors associated with hypertension (HT) in South Asian populations are relatively unknown. The objective of the current study was to investigate the prevalence rates of undiagnosed HT and factors associated with it in a cohort of males from the Central Province of Sri Lanka.MethodsThe study group consisted of 2462 males (mean age 31 years, range: 16–72 years) who underwent a routine medical examination at the National Transport Medical Institute, Kandy, Sri Lanka. Participants with previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 46 publications
6
17
4
1
Order By: Relevance
“…Another study [51] reported a 20.1% and 35.9% prevalence of obesity among men and women, respectively, which is much higher than our current findings. The prevalence of obesity among men in the Central province (12.3%) [46] and Kaluthara district (9.2%) [45] was also higher than our findings. However, Jayatissa et al [52] reported an obesity prevalence (15.2%) among women similar to the current study.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Another study [51] reported a 20.1% and 35.9% prevalence of obesity among men and women, respectively, which is much higher than our current findings. The prevalence of obesity among men in the Central province (12.3%) [46] and Kaluthara district (9.2%) [45] was also higher than our findings. However, Jayatissa et al [52] reported an obesity prevalence (15.2%) among women similar to the current study.…”
Section: Discussioncontrasting
confidence: 86%
“…The mean (SD) BMI of the total study population was 23.06 (4.2) kg/m 2 , which is similar to the average BMI reported by Ranasinghe et al (23.8 [4.2] kg/m 2 ) [28], but higher than the mean BMI observed in a national survey (21.8 [4.2] kg/m 2 ) [44] and in the Kaluthara district (22.9 [0.28] kg/m 2 ) for adults [45]. The mean BMI for men in the present study is similar to the average BMI for men reported using national (21.1 [3.7] kg/m 2 ) [8], provincial (Central Province, 22.7 [4.2] kg/m 2 [46]; four provinces, 21.5 [3.7] kg/m 2 [47]) and district (Colombo district, 22.8 [4.3] kg/m 2 [48]; Kaluthara district, 21.9 [0.46] kg/m 2 [45]) populations. Rathnayake et al [49] reported a higher average BMI for adult women than in our present study; conversely, the average BMI for women reported by Katulanda et al [8] (22.7 [4.5] kg/m 2 ) was lower than the current study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Hypertension in general is defined as systolic blood pressure above 140 mmHg and diastolic blood pressure above 90mmHg (1)(2)(3)(4) and it is a highly prevalent cardiovascular risk factor which if uncontrolled leads to devastating complications including myocardial infarction, strokes, chronic kidney disease and peripheral vascular disease (5). Prevalence of hypertension among adult females in United States is 28.1% (6) and it is more than a quarter of the entire population and it is expected to increase by 13% between 2000 and 2025 (7) making it a major contributing factor for cardiovascular disease, the leading cause of mortality among females (8,9) .…”
Section: Introductionmentioning
confidence: 99%